Case report: Recombinant human epidermal growth factor gel plus kangfuxin solution in the treatment of aplasia cutis congenita in a case with Adams–Oliver syndrome - Yang, Xiu-Fang; Shi, Shang-Wen; Chen, Kang (Frontiers in Surgery, 2023)
Background: Aplasia cutis congenita (ACC) (also known as congenital skin hypoplasia) is a condition where the presence of a large scalp defect can be potentially serious when complicated with hemorrhage and infection. Early healing of such a skin defect plays an important role in the prognosis of infants with this condition. Study case: A full-term newborn male was delivered with a round-shaped defect at the vertex of the scalp and skull (dimensions, 8 × 9 cm). The infant had a large deletion encompassing the 15.1 region of chromosome 15, including the DLL4 gene. Genetic testing was positive for Adams–Oliver syndrome (AOS). The skin defects of the scalp healed with recombinant human epidermal growth factor gel combined with kangfuxin solution therapy within two months. The infant had regular follow-up appointments. At the age of 5 months, the defect became smaller, hairless, and showed good granulation tissue. At 2 years of age, the child’s Gesell Developmental Schedules was 70. Conclusion: Recombinant human epidermal growth factor gel combined with kangfuxin solution was a successful conservative treatment for an infant with a large scalp defect accompanied by AOS.